Assessing Competitiveness and Real Exchange Rate Misalignment in Low-Income Countries - Lewis, Mark (IMF Working Papers; Working Paper ;, 2007)
Assessing a country's competitiveness routinely starts with an analysis of the real exchange rate. However, in low-income countries, empirical analysis of the real exchange rate is often subject to important limitations that seriously weaken the results. This paper summarizes the methodologies used to assess real exchange rate misalignments and discusses the range of obstacles common to low-income countries. Recognizing the importance of using a wide range of indicators for assessing competitiveness in low-income countries, the paper discusses alternative competitive measures and then proposes a template of indicators to allow for a systematic assessment of competitiveness in low-income countries. The template is then used to rank countries according to their competitiveness performance in 2006.